2012
DOI: 10.1016/j.tem.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue stem cells: the great WAT hope

Abstract: The past decade has witnessed an explosion in research into adipose tissue stem cells (ASCs), facilitated by their ease of isolation from white adipose tissue (WAT) and fueled by their therapeutic potential. Recent developments have extended ASC multipotency to include endodermal and ectodermal cell types, along with generation of induced pluripotent stem cells. This expanding multipotency has been paralleled by burgeoning translational applications, ranging from tissue engineering to anti-cancer therapy, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 103 publications
(128 reference statements)
0
84
0
Order By: Relevance
“…Subsequent studies confirmed and supplemented these findings with regard to ASCs in mice. The relatively high efficiency of iPS creation from ASCs may be partly due to the high expression of pluripotency factors in ASCs, such as basic-FGF, TGFβ, fibronectin and vitronectin [8]. Obtaining iPSs is methodologically complicated and expensive, so a natural source of pluripotent stem cells is constantly being searched for.…”
Section: The Potential and Directions Of Stem Cell Differentiationmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent studies confirmed and supplemented these findings with regard to ASCs in mice. The relatively high efficiency of iPS creation from ASCs may be partly due to the high expression of pluripotency factors in ASCs, such as basic-FGF, TGFβ, fibronectin and vitronectin [8]. Obtaining iPSs is methodologically complicated and expensive, so a natural source of pluripotent stem cells is constantly being searched for.…”
Section: The Potential and Directions Of Stem Cell Differentiationmentioning
confidence: 99%
“…Studies using in vitro conditions demonstrated their high plasticity and ability to differentiate into cells of ectodermal origin (neurons, oligodendrocytes and Schwann cells) and endodermal origin (pancreatic beta cells, hepatocytes and epithelial cells) [3,4,11,12]. The latest reports have extended our knowledge of the differentiation capability of ADSCs to include various types of epithelial cell, such as renal tubular epithelial cells and retinal pigment epithelial cells [8].…”
Section: The Potential and Directions Of Stem Cell Differentiationmentioning
confidence: 99%
See 3 more Smart Citations